2000
DOI: 10.1159/000010224
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration of Simple Pelvic Cysts during Pregnancy

Abstract: Traditional management of persistent ovarian cysts in pregnancy is explorative laparotomy at 16–20 weeks of gestation and resection of the tumor. Scheduling surgery to this time of pregnancy is accepted in order to prevent abortions that are common whenever surgery is done in the first trimester, without delaying treatment of ovarian tumors which harbor a malignant potential. In the following article we report of 10 cases where simple ovarian cysts diagnosed during pregnancy were successfully treated by sonogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Spontaneously resolved cases after delivery have been reported 15. As a non-surgical method, the drainage of simple cysts was performed successfully, and the authors confirmed the safety of the procedure 15 16…”
Section: Discussionmentioning
confidence: 78%
“…Spontaneously resolved cases after delivery have been reported 15. As a non-surgical method, the drainage of simple cysts was performed successfully, and the authors confirmed the safety of the procedure 15 16…”
Section: Discussionmentioning
confidence: 78%
“…Several authors advocate the ultrasound-guided aspiration of ovarian cysts, provided they strictly fulfill the criteria of benign cysts, including unilocular simple cyst, absence of papillary structures and/or the absence of any indicators for solid masses [15][16][17]. Recently, Whitecar et al demonstrated that adnexal masses considered to be benign on ultrasonographic imaging can be of low malignant potential after histopathological examination [1].…”
Section: Surgery For Adnexal Massesmentioning
confidence: 99%
“…In a series of 10 cases of fine needle aspiration of simple cysts in pregnancy, 5 resolved and there were no complications. 53 However, similar rates of simple cyst resolution have been observed in cases managed expectantly. Although cyst drainage is associated with a risk of infection, hemorrhage, and preterm labor, it may be appropriate in cases of suspected pelvic obstruction or mild symptoms.…”
Section: Surgical Managementmentioning
confidence: 64%